ANALISIS PENENTUAN UKURAN LOT PEMESANAN MENGGUNAKAN METODE JOINT ECONOMIC LOT SIZE (JELS) DI PT. FORESTALESTARI DWIKARYA TANJUNG PANDAN - Sodikin, Imam; Mudiarti, Ismi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
The development in industrial world brings a big effect in management of company. Supply chain management is the best solution for increasing prime competitive, with target inventory of management between buyer and supplier. On conventional inventory of management, vendor calculates lot size production policy independently like that with buyer. Optimize of Economic Order Quantity’s vendor not same with Economic Order Quantity of buyer. This problem can finish if there negotiation or joint policy (Joint Economic Lot Size). The examination aims to determine optimal joint policy between buyer and vendor. Result of analysis the set of contract number 1 is optimal for vendor with first order quantity (Q1) = 4,481.02 ton, z1 = Rp 24,590,458.32 and second order quantity (Q2) = 1,542.29 ton and z2 = Rp 847,232 with bargaining the vendor’s expected bargaining surplus is given by Rp 19,251,181.95 so, with this contract buyer and vendor gets profit’s.